20 Audit on the use of endomyocardial biopsy for diagnosis of non-transplant related cardiac conditions: single centre experience. (28th September 2016) - George, A; Moore, M; Lau, E; Roberts, M; Dixon, L; Herron, B; Owens, C
Abstract : Background: Endomyocardial biopsy (EMB) is an important tool, used in the diagnosis of a wide variety of cardiac conditions. While its role in the surveillance of post-cardiac transplant population is well recognised, its use in the diagnosis of non-transplant related cardiac conditions have not been adequately reported. We report a single centre experience of EMB for non-transplant related indications over a 5 year period. Results: A total of 50 EMBs were performed between January 2011 and December 2015.There has been a steady increase in the number of procedures performed during the observed period (Figure 1 ). The average age for patients undergoing EMB was 56.7 ± 15.1 years, with a significant majority being male (n = 39, 78%). Furthermore, majority of patients requiring EMB presented with symptoms of heart failure (Figure 2 ). Both femoral and internal jugular veins were used for access with the femoral route being more common (n = 46, 92%).Coronary angiography was performed in 40 (80%) patients. There was no significant difference in the average age between patients who underwent coronary angiography and who did not undergo angiography (56 ± 13.9 vs 59 ± 19.9, p = 0.558). Of the 40 patients who underwent coronary angiography, 11 (27.5%) underwent follow-on EMB. Likewise, cardiac MRI was performed in 40 (80%) patients. In all except one patient, cardiac MRI was performed prior to the EMB procedure. No procedural complications (procedure related mortality, requirement of pericardiocentesis or access related complications) were noted in any of the patients who underwent EMB. EMB provided diagnosis in 14 (28%) cases (Amyloidosis: 10, Lymphocytic myocarditis: 3, Sarcoidosis: 1). Out of the 10 cases of amyloidosis 2 were confirmed only following electron microscopic analysis. Cardiac MRI was indicative of amyloidosis in 8 of the 10 cases. However, it is also important to note that exclusion of specific pathological processes proved important in the management of these patients. Conclusion: Our findings demonstrate that the use of EMB for the diagnosis of non-transplant related cardiac conditions is increasing. Our experience demonstrates that the risk of procedural complication is low with none observed during the concerned period.